BATASAN USIA PERKAWINAN; SEBUAH TINJAUAN SOSIOLOGI HUKUM - Taufiqurohman, Taufiqurohman (USRATUNA: Jurnal Hukum Keluarga Islam, 2021)
The variety of positive laws governing the age limit for marriage is of particular concern to family law scholars. Harmonization of law can be done when looking at how the actual social character of the community in relation to the issues raised, namely finding the minimum age limit for marriage. The sociological-anthropological approach of law is used in this harmonization of law because the two blades actually use descriptive optics in viewing a problem. It is worth paying attention when determining the age limit must refer to several factors which are not only legal factors but also other factors and in order to provide legal certainty, justice and legal benefits, there must be an adjustment to the age limit, especially for children, for other laws and regulations.